2012
DOI: 10.1111/j.1460-6984.2011.00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Stroke patients communicating their healthcare needs in hospital: a study within the ICF framework

Abstract: About half of the stroke patients admitted into acute hospital stroke units had difficulty communicating their healthcare needs. Patients with more severe communication-related impairments had more severe difficulty communicating their healthcare needs. Future research is needed to understand the other factors that influence communication between people with communication disabilities and their healthcare providers in acute hospital settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 17 publications
0
21
0
3
Order By: Relevance
“…The team's charter was to critically evaluate stroke assessment and outcome measures within the World Health Organization's International Classification of Functioning, Disability and Health (ICF) framework [12][13][14][15][16][17][18][19][20]. This structure assured that the interdisciplinary team assessed the full spectrum of function from individual impairment to participation in society.…”
Section: Introductionmentioning
confidence: 99%
“…The team's charter was to critically evaluate stroke assessment and outcome measures within the World Health Organization's International Classification of Functioning, Disability and Health (ICF) framework [12][13][14][15][16][17][18][19][20]. This structure assured that the interdisciplinary team assessed the full spectrum of function from individual impairment to participation in society.…”
Section: Introductionmentioning
confidence: 99%
“…wanted this stuff… they [I] understood that this stuff, which was encurling [encouraging? ], they were [I was] beginning to say 'yeah' this stuff is good (20)." In these quotes, he used "they" but it was interpreted to mean that he was referring to himself, therefore, the implied meaning is included in parentheses.…”
Section: Treatment: "Challenge… Head… Helped Your Brain (P03 04)"mentioning
confidence: 99%
“…Other research has found that persons with aphasia have goals that align with the ICF. [18][19][20] An ICAP is structured to provide comprehensive care that addresses functional goals related to activity and participation. [18][19][20] Another model focuses specifically on aspects that contribute to living successfully with aphasia.…”
Section: Service Delivery For Aphasia Treatment In the United Statesmentioning
confidence: 99%
“…The provision of communication support also has the potential to increase the capacity of an individual with aphasia to express their healthcare needs, and participate in their own healthcare journey (O'Halloran, Worrall, & Hickson, 2012). For example, the provision of augmentative and alternative communication tools, communicative strategies, and techniques (Kagan, 1998) can facilitate an individual's ability to communicate their healthcare needs, including understanding their medical diagnosis, describing the medical history, asking questions about their care, telling care providers about pain or discomfort, and understanding descriptions of medical procedures (O'Halloran, Worrall, & Hickson, 2012).…”
Section: The Implications For People With Aphasia and Their Familiesmentioning
confidence: 99%
“…For example, the provision of augmentative and alternative communication tools, communicative strategies, and techniques (Kagan, 1998) can facilitate an individual's ability to communicate their healthcare needs, including understanding their medical diagnosis, describing the medical history, asking questions about their care, telling care providers about pain or discomfort, and understanding descriptions of medical procedures (O'Halloran, Worrall, & Hickson, 2012). Communicative support additionally has the potential to decrease the number of negative events within the hospital setting (Hemsley, Werninck, & Worrall, 2013).…”
Section: The Implications For People With Aphasia and Their Familiesmentioning
confidence: 99%